2010
DOI: 10.1007/s10661-010-1326-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of subsurface drainage on waterlogged and saline lands

Abstract: Waterlogging and salinity due to seepage from canals have polluted land and environment in various parts of Pakistan. A sustainable environment requires urgent remedial measures for this problem. The research in this paper presents the impacts of the Fourth Drainage Project, Faisalabad on the twin problem of waterlogging and salinity. Monitoring of the project was made on regular basis. The key performance indicators for the project include the lowering of water table, improvement of water quality and soil sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…This is quite considerable if extended onto farmland scale, as 3.68 ton ha −1 of salt could be removed under the same condition in 25 days. Previous researches investigated salt removal performance by the technique of subsurface perforated pipe for saltwater drainage (Ghumman, Ghazaw, Niazi, & Hashmi, 2011; Haj‐Amor & Bouri, 2019; Kelleners & Chaudhry, 1998; Lu et al, 2018; Zhu et al, 2018). Zhu et al (2018) conducted a 2‐year experiment and concluded that the best salt removal performance was in 0–1 m tillage layer when the buried depth of the perforated pipe was 1.5 m among 3 different buried depths (i.e., 1.2 m, 1.5 m and 1.8 m) in Xinjiang Province, China, salinity decreased 8.9 g kg −1 .…”
Section: Resultsmentioning
confidence: 99%
“…This is quite considerable if extended onto farmland scale, as 3.68 ton ha −1 of salt could be removed under the same condition in 25 days. Previous researches investigated salt removal performance by the technique of subsurface perforated pipe for saltwater drainage (Ghumman, Ghazaw, Niazi, & Hashmi, 2011; Haj‐Amor & Bouri, 2019; Kelleners & Chaudhry, 1998; Lu et al, 2018; Zhu et al, 2018). Zhu et al (2018) conducted a 2‐year experiment and concluded that the best salt removal performance was in 0–1 m tillage layer when the buried depth of the perforated pipe was 1.5 m among 3 different buried depths (i.e., 1.2 m, 1.5 m and 1.8 m) in Xinjiang Province, China, salinity decreased 8.9 g kg −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Open ditch has obvious advantage for the removal of excess water from the land surface, but it occupies much farmland. Subsurface pipe drainage occupies less farmland and has advantages in preventing soil erosion and reducing non-point pollution and improving soil aeration and increasing crop yield (Azhar and Latif, 2011;Coelho et al, 2010;Darzi-Naftchali and Shahnazari, 2014;Ghumman et al, 2010;Grazhdam et al, 1996;Maalim et al, 2013;Sharma and Gupta, 2006). These characteristics of subsurface pipe drainage also match the 2014 farmland protection policy of China.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, the influence of evaporation on groundwater F − concentration is lowered while fluoride is lost from high-fluoride areas along with surface runoff. The approach of reducing groundwater levels by excavating ditches to drain shallow groundwater to surface runoff has already been practiced for the treatment of saline-alkali land [72,73]. However, many challenges persist in achieving the goal of in situ treatment due to the active chemical properties of fluoride, such as the characteristics of fluoride leaching from shallow high-fluoride soils and its transport in shallow water-soil systems.…”
Section: Introduction Of In Situ Treatmentmentioning
confidence: 99%